Japan Stroke Society Guideline 2021 for the Treatment of Stroke. Issue 9 (October 2022) - Miyamoto, Susumu; Ogasawara, Kuniaki; Kuroda, Satoshi; Itabashi, Ryo; Toyoda, Kazunori; Itoh, Yoshiaki; Iguchi, Yasuyuki; Shiokawa, Yoshiaki; Takagi, Yasushi; Ohtsuki, Toshiho; Kinouchi, Hiroyuki; Okada, Yasushi; et al.
The revised Japan Stroke Society Guidelines for the Treatment of Stroke were published in Japanese in July 2021. In this article, the extracted recommendation statements are published. The revision keeps pace with the great progress in stroke control based on the recently enacted Basic Act on Stroke and Cardiovascular Disease in Japan. The guideline covers the following areas: primary prevention, general acute management of stroke, ischemic stroke and transient ischemic attack, intracerebral hemorrhage, subarachnoid hemorrhage, asymptomatic cerebrovascular disease, other cerebrovascular disease, and rehabilitation.